A longitudinal study of antenatal and perinatal risk factors in early childhood cognition: Evidence from Growing Up in New Zealand - Neumann, Denise; Herbert, Sarah E.; Peterson, Elizabeth R.; Underwood, Lisa; Morton, Susan M.B.; Waldie, Karen E. (Early human development, 2019)
Poor maternal health, disadvantageous exposures during pregnancy and unfavourable perinatal events are associated with adverse trajectories in offspring cognitive development. To examine longitudinal associations between antenatal maternal, perinatal and maternal health characteristics and children's early cognitive development across executive control, motor ability and receptive language domains. Analyses comprised interview and observational data from 4587 children and their mothers enrolled in the longitudinal Growing Up in New Zealand cohort study. Children's executive control (Luria hand clap task), motor skills (mothers' report) and receptive language ability (Peabody Picture Vocabulary Test) were assessed at age 4.5 years. Multivariate logistic regression analyses were conducted, controlling for sociodemographic factors. Smoking pre- and during pregnancy, no folate intake during first trimester and low birth weight were risk factors for poorer executive control. Perceived stress during pregnancy, no folate intake during first trimester and low birth weight were all risk factors for poorer motor ability. Smoking pre-pregnancy, antenatal anxiety and no folate intake during first trimester were risk factors for poorer receptive language ability. Adverse ante- and perinatal environments are associated with poorer executive control, motor and receptive language abilities in early childhood. Improving maternal education and support especially for more disadvantaged mothers during pregnancy may reduce the potential deleterious impact of adverse ante- and perinatal conditions on children's early cognition. •4587 children of a longitudinal study who had adverse perinatal environments had an increased likelihood of poor cognitive abilities at 4.5 years.•Smoking during pregnancy, no folate intake during first trimester and low birth weight were risk factors for poor executive control.•Perceived stress during pregnancy, no folate intake during first trimester and low birth weight were all risk factors for poor motor ability.•Smoking pre-pregnancy, antenatal anxiety and no folate intake during first trimester were risk factors for poor receptive language ability.